PENGEMBANGAN MEDIA FLASHCARD BERBASIS KEARIFAN LOKAL SUMATRA UTARA PADA MATERI INDONESIAKU KAYA BUDAYA KELAS IV SD - Miftah Aulia Zahrani; Nurmairina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to develop flashcard media based on North Sumatra local wisdom that is feasible in the IPAS subject matter of “Indonesiaku Kaya Budaya”, strengthening students' knowledge of local wisdom in North Sumatra. This research is a type of research (Research and Development) using the ADDIE development model. The instrument used to collect data is a questionnaire or questionnaire given to media expert validators, material expert validators, teachers and students. This research uses five stages: (1) analysis stage, which involves analysis the needs for learning media, student analysis (situation) and material analysis. (2) the design stage, which involves designing products that are in accordance with the needs. (3) the development stage, which involves creating designs that is in accordance with the material. The subjects in this study were material expert validators and media expert validators. Based on the data analysis obtained through the material expert validity test, the percentage of 87% categorized as very valid/very appropriate. While the media expert validator obtained a percentage of 88% categorized as very very valid/very appropriate. (4) The implementation stage involves conducting research directly to schools to get teacher responses and student responses to the flashcard media that has been developed. Based on the data analysis obtained through the teacher response questionnaire, a percentage of 86% was obtained, categorized as very valid/very appropriate. Through the student response questionnaire, a percentage of 84% - 100% was obtained from 6 students and 64% - 83.9% from 21 students. These results state that flashcard learning media based on local wisdom of North Sumatra can provide new information, make it easier for students to understand the material, increase learning motivation, encourage interest in learning, attract attention, are fun, easy and safe to use. (5) the evaluation stage, at this stage it was concluded that the flashcard media based on North Sumatra's local wisdom on the material of “Indonesiaku Kaya Budaya” for grade IV is declared very valid/very appropriate to use in the learning process.